Understanding the Learning Challenges of English-Medium Instruction Learners and Ways to Facilitate Their Learning: A Case Study of Taiwan Psychology Students' Perspectives - Tzu-Ling Hua (Universidad de La Sabana, 2020)
Entender los desafíos de aprendizaje de los estudiantes de asignaturas en inglés y formas de facilitar su aprendizaje: un estudio de caso de las perspectivas de estudiantes de psicología de Taiwán Compreender os desafios da aprendizagem dos alunos de disciplinas em inglês e maneiras de facilitar seu aprendizado: um estudo de caso das perspectivas de estudantes de psicologia de Taiwan English-medium instruction (EMI) has become a global education phenomenon in recent decades, especially in higher education. However, its implementation is still facing criticism. On the one hand, learners are welcoming the envisaged benefits of preparing them with professional content knowledge and English language proficiency to compete in the new global economy; on the other hand, they are reluctant to take the courses because of the challenges and difficulties EMI creates. Meanwhile, EMI lecturers are concerned about students' inability to survive, or better still thrive through EMI learning. EMI lecturers are experts in their professional domain but are not trained or prepared to teach EMI courses yet. This qualitative study examines the perception of first-year undergraduate students taking the EMI foundation psychology course in Taiwan, focusing on their perspectives of factors facilitating or hindering their EMI learning, and their suggestions for improving the situation. The results not only point out what kinds of teaching practices contribute to challenges for EMI learners in their learning process but also the underlying reasons and the pedagogy practice that students suggest can be used to improve the situation. Insights provided by this study can be used to assist EMI lecturers in examining their pedagogical practice and expand their knowledgeability about pedagogy. They can also be used as a way forward for assisting in the development of EMI teacher training and professional development, and the implementation of EMI. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Hua, T-L. (2019). Understanding the Learning Challenges of English-Medium Instruction Learners and Ways to Facilitate Their Learning: A Case Study of Taiwan Psychology Students' Perspectives. Latin American Journal of Content & Language Integrated Learning, 12(2), 321-340. https://doi.org/10.5294/laclil.2019.12.2.6 Received: 22/09/2019 Approved: 20/02/2020 Published: 11/05/2020